Cutaneous blood flow during exercise is higher in endurance-trained humans - Fritzsche, R. G.; Coyle, E. F. (Journal of Applied Physiology, 2000)
This study determined whether cutaneous blood flow during exercise is different in endurance-trained (Tr) compared with untrained (Untr) subjects. Ten Tr and ten Untr men (62.4 ± 1.7 and 44.2 ± 1.8 ml · kg1 · min1, respectively; P < 0.05) underwent three 20-min cycling-exercise bouts at 50, 70, and 90% peak oxygen uptake in this order, with 30 min rest in between. The environmental conditions were neutral (~23-24°C, 50% relative humidity, front and back fans at 2.5 m/s). Because of technical difficulties, only seven Tr and seven Untr subjects completed all forearm blood flow and laser-Doppler cutaneous blood flow (CBF) measurements. Albeit similar at rest, at the end of all three exercise bouts, forearm blood flow was ~40% higher in Tr compared with Untr subjects (50%: 4.64 ± 0.50 vs. 3.17 ± 0.20, 70%: 6.17 ± 0.61 vs. 4.41 ± 0.37, 90%: 6.77 ± 0.62 vs. 5.01 ± 0.37 ml · 100 ml1 · min1, respectively; n = 7; all P < 0.05). CBF was also higher in Tr compared with Untr subjects at all relative intensities (n = 7; all P < 0.05). However, esophageal temperature was not different in Tr compared with Untr subjects at the end of any of the aforementioned exercise bouts (50%: 37.8 ± 0.1 vs. 37.9 ± 0.1°C, 70%: 38.1 ± 0.1 vs. 38.1 ± 0.1°C, and 90%: 38.8 ± 0.1 vs. 38.6 ± 0.1°C, respectively). We conclude that a higher CBF may allow Tr subjects to achieve an esophageal temperature similar to that of Untr, despite their higher metabolic rates and thus higher heat production rates, during exercise at 50-90% peak oxygen uptake.